2017
DOI: 10.3390/en10091272
|View full text |Cite
|
Sign up to set email alerts
|

An Electro-Geometric Model for Lightning Shielding of Multiple Wind Turbines

Abstract: Wind turbine blades being struck by lightning is one of the most urgent problems facing wind farms. In order to reduce the probability of lightning accidents on wind farms, this paper presents a new electro-geometric model for multiple turbines. In this new model, based on the physical model of lightning leader development, the striking distance range of the blade tip receptor is calculated, taking into account the influence of the charged particles around the blade. Lightning shielding amongst multiple turbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For example, L. Zhang et al. (2017) used an improved electrical geometric model to study the lightning protection distance of WTCs. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, L. Zhang et al. (2017) used an improved electrical geometric model to study the lightning protection distance of WTCs. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of WTCs have mostly focused on the influence of different blade angles and the distance between WTs on the shielding effect. For example, L. Zhang et al (2017) used an improved electrical geometric model to study the lightning protection distance of WTCs. Liu et al (2020) discussed the influence of the blade angle on the shielding effect by using a finite element physical field.…”
mentioning
confidence: 99%
“…The analysis showed that the blade rotation could be altering the charge distribution on the blade tip, resulting in varied ascending leader development on the blade tip, which affected the discharge development process. Zhang et al [27] presented a new electro-geometric model for multiple turbines, and the calculation results showed that the larger the relative air density and the absolute humidity and the lower the altitude, the larger the lightning shielding distance between wind turbines. Zhou et al [28] studied the lightning attachment process of a full-scale wind turbine blade and downward leader; the results showed that the interception was more effective when the cross-sectional area of the receptor was in accordance with the minimum value of 50 mm 2 , and the interception effect could not be improved significantly when the number of receptors was increased.…”
Section: Introductionmentioning
confidence: 99%